Rice husk derived waste materials as partial cement replacement in lightweight concrete Utilização de resíduos derivados da casca de arroz como substitutos parciais do cimento no concreto leve - Celso Yoji Kawabata; Holmer Savastano Junior; Joana Sousa-Coutinho (Ciência e Agrotecnologia, 2012)
In this study rice husk ash (RHA) and broiler bed ash from rice husk (BBA), two agricultural waste materials, have been assessed for use as partial cement replacement materials for application in lightweight concrete. Physical and chemical characteristics of RHA and BBA were first analyzed. Three similar types of lightweight concrete were produced, a control type in which the binder was just CEMI cement (CTL) and two other types with 10% cement replacement with, respectively, RHA and BBA. All types of similar lightweight concrete were prepared to present the same workability by adjusting the amount of superplasticizer. Properties of concrete investigated were compressive and flexural strength at different ages, absorption by capillarity, resistivity and resistance to chloride ion penetration (CTH method) and accelerated carbonation. Test results obtained for 10% cement replacement level in lightweight concrete indicate that although the addition of BBA conducted to lower performance in terms of the degradation indicative tests, RHA led to the enhancement of mechanical properties, especially early strength and also fast ageing related results, further contributing to sustainable construction with energy saver lightweight concrete. Neste trabalho, cinzas de casca de arroz (RHA) e cinzas de cama de frango (BBA), dois resíduos agrícolas, foram avaliadas para uso como substitutos parciais do cimento para produção de concreto leve. Características físicas e químicas de RHA e BBA foram analisadas. Três tipos semelhantes de concreto leve foram produzidos, um controle em que o ligante era totalmente cimento CEM I (CTL) e dois outros tipos de concreto, com substituição de 10% com RHA e BBA, respectivamente. Todos os tipos de concreto leve foram feitos através do ajuste da quantidade de superplastificante para apresentarem a mesma trabalhabilidade. Propriedades de concreto investigados foram resistência à compressão e à flexão em diferentes idades, a absorção por capilaridade, resistividade e resistência à penetração de íons cloreto (método CTH) e carbonatação acelerada. Os resultados dos testes obtidos para o nível de 10% de de substituição de cimento em concreto leve indicam que, embora a adição de BBA tenha conduzido a desempenho inferior em termos dos testes indicativos de degradação, a RHA levou à melhoria das propriedades mecânicas, especialmente resistência inicial e também resultados relacionados ao envelhecimento acelerado, contribuindo para a construção sustentável.